2004
DOI: 10.1183/09031936.03.00038403
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and proliferation in lungs of ventilated and oxygen-treated preterm infants

Abstract: . ABSTRACT: Apoptosis and proliferation and the effect of exogenous surfactant on these processes were investigated in the lungs of mechanically ventilated/oxygen-treated preterm infants with respiratory distress syndrome and stillborn foetuses.Apoptotic and proliferation indices were determined in lung tissue sections from 27 ventilated/oxygen-treated preterm infants and 29 stillborn foetuses. The effect of exogenous surfactant on apoptosis and proliferation was studied in 16 ventilated preterm infants; 11 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 36 publications
(60 reference statements)
2
45
1
Order By: Relevance
“…Apparently, the development of BPD can be primed by exposure to prenatal pulmonary inflammation, which can be aggravated by postnatal events (8,52,53). Structural changes by apoptosis of parenchymal cells were induced in the course of injury and inflammation in the airways and lungs (54). Apparently, alveolar inflammation affects endothelial function and angiogenesis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the development of BPD can be primed by exposure to prenatal pulmonary inflammation, which can be aggravated by postnatal events (8,52,53). Structural changes by apoptosis of parenchymal cells were induced in the course of injury and inflammation in the airways and lungs (54). Apparently, alveolar inflammation affects endothelial function and angiogenesis (8).…”
Section: Discussionmentioning
confidence: 99%
“…In this rheostat, ceramide stimulates apoptosis and cell cycle arrest, and sphingosine-1-phosphate stimulates cell survival and proliferation. Increased apoptosis has been found in epithelial cells of BPD patients [8] and in animal models of BPD [9], and total lung ceramide levels are upregulated in hyperoxia-exposed neonatal rats [10]. To date, no detailed analysis of the sphingolipid metabolome in the hyperoxia-induced BPD model [11] has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The main pathological hallmark of BPD is an arrest of alveolar development, characterized by large and simplified distal airspaces (4,5). In addition, several recent reports have shown that the lungs of ventilated preterm infants with early BPD show markedly increased levels of alveolar epithelial cell death (6)(7)(8).…”
mentioning
confidence: 99%